1988
DOI: 10.1002/hep.1840080313
|View full text |Cite
|
Sign up to set email alerts
|

Experimental duck hepatitis B virus infection: Pathology and evolution of hepatic and extrahepatic infection

Abstract: Seventy, 1-day-old ducklings inoculated intraperitoneally with duck hepatitis B virus and 30 controls have been studied over a 2-year period. Infection with duck hepatitis B virus occurred in all inoculated ducks, although this was not associated with clinical morbidity. Duck hepatitis B virus DNA was first detected in liver on Day 3, in pancreatic acinar cells on Day 4, serum on Day 6, splenic red and white pulp on Day 7 and in the renal glomurulus on Day 14, using a combination of dot, Southern blot and in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

1990
1990
2007
2007

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 57 publications
(35 citation statements)
references
References 26 publications
(11 reference statements)
2
33
0
Order By: Relevance
“…The primary duck hepatocytes or primary IBDE cells at day 1 of culture were inoculated with 100 viral genome equivalents (vge)/ml of DHBV (Australia strain) derived from pooled duckling sera (4,12). The cells were incubated for 2 h with occasional rocking prior to the addition of growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…The primary duck hepatocytes or primary IBDE cells at day 1 of culture were inoculated with 100 viral genome equivalents (vge)/ml of DHBV (Australia strain) derived from pooled duckling sera (4,12). The cells were incubated for 2 h with occasional rocking prior to the addition of growth medium.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3][4][5] In particular, the duck on liver histology and expression of viral markers of replication. model has facilitated the study of the basic molecular virology Nineteen animals underwent BDL and fourteen animals served as of the Hepadnaviridae, including the replication strategy 2,6 unligated controls.…”
Section: Materials and Methods Division Does Not Reduce The Viral Burmentioning
confidence: 99%
“…These different outcomes are viral dose dependent; persistent infection in young ducks develops more frequently with higher doses of virus [92] . In some cases, dependent on age and infection with a given mutant, experimental infections can cause symptoms of a liver inflammation [93] . It has been shown that one genome equivalent is sufficient to infect a duckling and that spread of the virus within the liver is very efficient: 14 d after inoculation, virtually all hepatocytes were infected [94] .…”
Section: In Vitro Infectionmentioning
confidence: 99%